Who benefits from tuition-free, top-quality universities? Evidence from Brazil - Suzanne Duryea; Rafael Pérez Ribas; Breno Sampaio; Gustavo R. Sampaio; Giuseppe Trevisan (Inter-American Development Bank (IDB), 2023)
This paper investigates the long-term impact on earnings of attending a tuition-free, top-quality university in Brazil. We identify the causal effect through a sharp discontinuity in an admission process based on test scores. If admitted, low-income students are found to increase their earnings by 26% ten years later. However, admission has a small and insignificant effect on high-income students. The difference between income groups is not explained by educational attainment, program choice, or selection into better-paying jobs. The evidence suggests that most low-income applicants, if not admitted, still graduate from college but with much lower returns to education. Highincome applicants who just miss the cutoff, however, can find other opportunities such that earnings trajectories are unchanged. Our results underscore the role of affordable higher education in promoting social mobility.
Keywords: H52; I23; I26; 330; College wage premium; affordability; school quality; income groups